Advanced tools for smartphone-based experiments: phyphox. (16th May 2018) - Staacks, S; Hütz, S; Heinke, H; Stampfer, C
Abstract: The sensors in modern smartphones are a promising and cost-effective tool for experimentation in physics education, but many experiments face practical problems. Often the phone is inaccessible during the experiment and the data usually needs to be analyzed subsequently on a computer. We address both problems by introducing a new app, called 'phyphox', which is specifically designed for utilizing experiments in physics teaching. The app is free and designed to offer the same set of features on Android and iOS.